The pCoo Plasmid of Enterotoxigenic Escherichia coli Is a Mosaic Cointegrate - Froehlich, Barbara (American Society for Microbiology, 2005)
CS1 is the prototype of a class of pili of enterotoxigenic Escherichia coli (ETEC) associated with diarrheal disease in humans. The genes encoding this pilus are carried on a large plasmid, pCoo. We report the sequence of the complete 98,396-bp plasmid. Like many other virulence plasmids, pCoo is a mosaic consisting of regions derived from multiple sources. Complete and fragmented insertion sequences (IS) make up 24% of the total DNA and are scattered throughout the plasmid. The pCoo DNA between these IS elements has a wide range of G+C content (35 to 57%), suggesting that these regions have different ancestries. We find that the pCoo plasmid is a cointegrate of two functional replicons, related to R64 and R100, which are joined at a 1,953-bp direct repeat of IS100. Recombination between these repeats in the cointegrate generates the two smaller replicons which coexist with the cointegrate in the culture. Both of the smaller replicons have plasmid stability genes as well as genes that may be important in pathogenesis. Examination by PCR of 17 other unrelated CS1 ETEC strains with a variety of serotypes demonstrated that all contained at least parts of both replicons of pCoo and that strains of the O6 genotype appear to contain a cointegrate very similar to pCoo. The results suggest that this family of CS1-encoding plasmids is evolving rapidly.